Anterior Canal Reconstruction and Fusion for Myelopathy Caused by Degenerative Cervical Kyphosis and Stenosis With or Without Ossification of the Posterior Longitudinal Ligament. Issue 1 (February 2022) - Yang, Haisong; Sun, Yuling; Wang, Liang; Guo, Qunfeng; Jiang, Jingjing; Lu, Xuhua
Abstract : Study Design: This was a retrospective study. Objective: To introduce an anterior surgical technique for myelopathy caused by degenerative cervical kyphosis and stenosis (DCKS) with or without ossification of the posterior longitudinal ligament (OPLL). Summary of Background Data: The optimal approach in the treatment of DCKS remains a controversy because each anterior or posterior route surgery has advantages and disadvantages. Materials and Methods: In the period from June 2017 through June 2019, a consecutive cohort of adults diagnosed with DCKS underwent anterior canal reconstruction and fusion (ACRF). All patients underwent x-ray, computed tomography, and magnetic resonance imaging of the cervical spine. Radiologic assessment included kyphosis, canal area, canal reconstruction, OPLL, and spinal cord curvature and morphology. The Japanese Orthopaedic Association (JOA) scoring system was used to evaluate the neurological status. Surgery-related and implant-related complications were all recorded. Follow-up was carried out at 3, 6, 12, 24, and 36 months postoperation. Results: Fourty-one patients were included in the study, of which 19 presented with OPLL. Postoperatively, the canal area were significantly greater at last follow-up compared with preoperation (208.4 vs. 123.2 mm 2 ; P =0.001). There was significant kyphosis correction (−17.6 vs. 8.5 degrees, P =0.001) at last follow-up. Ninety-six segmental canal reconstruction were performed, 89 (92.7%) reached bone fusion at both grooves with a mean time of 7.9 months. On sagittal magnetic resonance imaging, 33 (80.5%) patients presented with lordosis in the spinal cord curvature, 8 (19.5%) with straight. The mean JOA score at last follow-up was significantly better than preoperation (15.0 vs. 9.3 points; P <0.01). One patient presented with cerebrospinal fluid leakage, 1 with screw displacement and 2 with dysphagia. Conclusion: ACRF, receiving good correction of kyphosis, amplified canal area, solid instrumented fusion and circumferential decompression, is an effective and safe surgical technique for cervical myelopathy caused by DCKS with or without OPLL. Level of Evidence: Level III—a retrospective analysis.